Snowhook - Storm, Jo, 1972- (Dundurn, 2019)
A massive snow storm traps fourteen-year-old Hannah and her family in their mountain cabin. When an accident with her mother's insulin occurs, Hannah must harness her sled dogs and make for their closest neighbor who has a phone. After a wrong turn in worsening weather, not to mention an unexpected passenger, Hannah must use all the survival skills she knows if she is to save her mother and herself.